Air Quality and Health Impacts of Freight Modal Shifts: Review and Assessment. Issue 3 (March 2019) - Ramani, Tara; Jaikumar, Rohit; Khreis, Haneen; Rouleau, Mathieu; Charman, Nick
Freight movement is a significant and growing contributor to transportation emissions globally. Modal shifts in freight, that is, moving freight from a higher emission mode to one associated with lower emissions, are discussed as a strategy to reduce emissions of criteria pollutants and greenhouse gases (GHGs). However, there is limited knowledge of the magnitude of potential benefits and their impacts on human health. The overall goal of this study is to identify and characterize the potential of modal shifts in freight transport for mitigating air pollutant emissions, air pollutant concentrations, population exposure to air pollutants, and health impacts. The analysis was conducted in the Canadian context, with a focus on land-based freight such as trucks, trains, and pipelines, as well as marine shipping for inland and coastal waters. A structured review of the existing literature database, and a critical assessment of the findings was conducted, using a weight-of-evidence approach. The assessment took into consideration potential local and regional variables for Canada. The results indicated that there is limited evidence that road-to-rail, road-to-marine, and rail-to-marine modal shifts could reduce pollutant and GHG emissions. There was insufficient evidence on modal shifts involving the pipeline mode, and on the air quality, population exposure, and health impacts related to any modal shift. Several research gaps remain, which must be addressed establish the emissions, air quality, and health impacts of freight modal shifts.